Specific Autoantibodies and Clinical Phenotypes Correlate with the Aberrant Expression of Immune-Related MicroRNAs in Dermatomyositis - Lifang Ye; Yu Zuo; Hanbo Yang; Wenli Li; Qinglin Peng; Xin Lu; Guochun Wang; Xiaoming Shu (Journal of Immunology Research)
Aims. The serum concentrations of miRNAs, miR-23a-3p, miR-23b-3p, miR-146a-5p, miR-146b-5p, and miR-150-5p, were shown to be associated with the immune and inflammatory progressions. We assessed the expressions of these five miRNAs in association with clinical phenotypes and myositis-specific autoantibody-defined subgroups of dermatomyositis (DM). Methods. The present study included 49 patients with DM and 30 healthy controls. The serum concentrations of miR-23a-3p, miR-23b-3p, miR-146a-5p, miR-146b-5p, and miR-150-5p were measured by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Associations between the serum concentrations of miRNAs and DM clinical immune phenotypes were examined as well. Results. The serum concentrations of miR-23b-3p, miR-146a-5p, and miR-150-5p were significantly downregulated in DM patients (P<0.001, P<0.001, and P=0.002, respectively), while miR-146b-5p was remarkably upregulated in DM patients compared with healthy controls (P=0.039). Similarly, the expressions of miR-23b-3p, miR-146a-5p, and miR-150-5p were significantly downregulated in the peripheral blood mononuclear cells (PBMCs) from DM patients. Further study indicated that the serum level of miR-23b-3p was significantly correlated with creatine kinase (CK) (r=−0.286, P=0.046) and the serum level of miR-146a-5p was evidently correlated with C-reactive protein (CRP) (r=−0.358, P=0.012). Significant correlations were also observed between the serum levels of miR-146b-5p and CRP (r=−0.347, P=0.014) and the erythrocyte sedimentation rate (ESR) (r=−0.287, P=0.046). In addition, the expression level of miR-146b-5p was upregulated in DM complicated by tumors compared with those without tumors (P=0.001 and P<0.001, respectively). Especially, miR-150-5p was significantly downregulated in DM patients with anti-MDA5 antibodies and anti-NXP2 antibodies compared with those without (P=0.017 and P=0.047, respectively). No significant differences were observed between the four serum microRNAs in patients with and without interstitial lung diseases (all P>0.05). Conclusion. The results suggest an association between the four immune-related microRNAs and different clinical immune-phenotypes, and this association may regulate the complexity of disease processes through multipathways in DM patients.